Evaluation of performance and fouling resistance of sandwich ultrafiltration for treatment of final discharged palm oil mill effluent(no full stop in abstract) - Mazlan, Nurul Ain (2018)
Oil palm is the important agriculture industry in Malaysia which consumed hundreds tonnes of water for the proses and 50% of which ends up as effluent. However, water can be sustained and conserved by treating final discharged and recycle back to the plant. Membrane ultrafiltration has been proven a reliable tool in treating wastewater, therefore, it is a promising green technology to treat final discharged from palm oil mill. Thus, this work is carried out to evaluate the effectiveness of ultrafiltration in reclaiming water from final discharged palm oil mill effluent (POME) as well as to investigate the fouling of membrane. Two types of membrane used were polyethersulfone (PES) and regenerated cellulose (RC) of 5kDa and 10 kDa. The first part of this study is to evaluate the effect of parameters that are: pressure (0.5 bar, 1.0 bar, 1.5 bar, 2.0 bar), stirring speed (0 rpm, 400 rpm, 600 rpm, 800 rpm) and pH value (6, 7, 8, 10) on ultrafiltration treatment and fouling resistance. The appropriate filtration condition was recognized and the permeate was further analysed for COD, BOD5 and suspended solid. Based on the parametric study, selected condition was fixed for the second part to evaluate the effect of sandwich configuration to further improve the final discharged quality and to analyse fouling resistance. Cake layer resistance was found to be dominant for all membranes tested. Two flat membranes were sandwiched together with both effective layer facing up (SS) or the effective layer of the bottom membrane facing down (SB) The results showed of the best permeate quality was achieved with 5 kDa PES membrane at pressure 1.0 bar, 600 rpm and pH 8: the reduction of COD, BOD5, turbidity, and total dissolved solid were 67.3%, 72.47%, 94.2% and 40% respectively. For sandwich membrane, interestingly, SS-sandwich showed the best permeate quality with pollutant reduction up to 80-90% (PES 5kDa) compared to 60-70% for single membrane. The quality of permeate from SS-sandwich membrane of 5 kDa was beyond reuse standard and approaching drinking water standard for TSS, TDS and turbidity. Therefore it can be concluded that, with the appropriate arrangement of sandwich membrane and operating condition, water reuse which successfully complies with World Health Organization (WHO) standard can be reclaimed from POME using UF technique.